Mutagenesis of specificity and toxicity regions of a Bacillus thuringiensis protoxin gene. - Aronson, A I (1995)
Two different 30-nucleotide regions of the cryIAc insecticidal protoxin gene from Bacillus thuringiensis were randomly mutagenized. One region was within one of seven amphipathic helices believed to be important for the formation of ion channels. There was no loss of toxicity for three test insects by any of 27 mutants, a result similar to that obtained previously for mutations within another such helix. Only mutations within a region encoding the central helix have resulted in a substantial number of mutants with low or no toxicity. A second mutagenized region encodes amino acids which are unique to this toxin and are within one of the loops in a portion of the toxin important for specificity. Among 21 different mutations of these 10 residues, only changes of two adjacent serine residues resulted in decreased toxicity which was greater for Manduca sexta than for Heliothis virescens larvae. These mutant toxins bound poorly to the single M. sexta CryIAc vesicle-binding protein and to several of the multiple H. virescens-binding proteins. The loop containing these serines must be involved in the formation of a specific toxin recognition domain.